DAMPAK PEREKONOMIAN KELUARGA PADA STATUS GIZI ANAK DI DESA AIKMEL UTARA, KECAMATAN AIKMEL, KABUPATEN LOMBOK TIMUR - saskia amal diniyah; Prof. Dr. Joni Rokhmat. M.Si (Postgraduate Program, University of Mataram, 2025)
The family's economic condition has a significant impact on children's nutritional status, especially in rural areas. This study aims to analyze the relationship between family economic conditions and children's nutritional status in Aikmel Utara Village, Aikmel District, East Lombok Regency. The research method used is a descriptive survey with a quantitative approach. Data were obtained through interviews and anthropometric measurements of toddlers. The results showed that although most families had sufficient income, many children still experienced malnutrition and stunting due to improper dietary patterns and low parental knowledge about nutrition. Intervention efforts in the form of nutrition education and improved parenting patterns are needed to enhance children's nutritional status in this area.